2007
DOI: 10.1177/1081180x07307190
|View full text |Cite
|
Sign up to set email alerts
|

The Media's Role in a Clash of Misconceptions: The Case of the Danish Muhammad Cartoons

Abstract: The Danish cartoon furor of early 2006 was only the most recent episode cited as evidence of a “clash of civilizations.” Although the subject was extensively reported by the global media, the media's framing of the debate as being between free speech and religious sensitivities was inherently flawed and contributed to further confusion rather than clarification. Moreover, the framework established and perpetuated by the media, that of a debate between freedom of speech and religious sensitivities, obscured the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 7 publications
0
27
0
1
Order By: Relevance
“…As reported by some studies, those factors that have ever made Muslim attain considerable prominence and salience as a social category are, among other things, the Rushdie Affair in 1988-89, the first Gulf war in 1991, and the September 11th, controversial Danish caricature of Prophet Muhammad (Ahmad & Evergeti, 2010;Hussain, 2007;Modood & Ahmad, 2007;Peek, 2005). All of these events in essence are not in favor of Muslims and thus threaten their existence, from which Muslims' negative attitudes and stereotyping against Western countries eventually emerge (Murshed, 2010).…”
Section: Figura 3b High Identity Saliencementioning
confidence: 98%
“…As reported by some studies, those factors that have ever made Muslim attain considerable prominence and salience as a social category are, among other things, the Rushdie Affair in 1988-89, the first Gulf war in 1991, and the September 11th, controversial Danish caricature of Prophet Muhammad (Ahmad & Evergeti, 2010;Hussain, 2007;Modood & Ahmad, 2007;Peek, 2005). All of these events in essence are not in favor of Muslims and thus threaten their existence, from which Muslims' negative attitudes and stereotyping against Western countries eventually emerge (Murshed, 2010).…”
Section: Figura 3b High Identity Saliencementioning
confidence: 98%
“…), and this loss of context makes the situation ripe for misunderstandings and interpretations (cf. Hussain, 2007). Decontextualization can also be seen as part of the logic noted by Durham Peters (2008) in which particular subject matter tends to be subsumed under the freedom of expression heading.…”
Section: Resultsmentioning
confidence: 99%
“…Why have political cartoons become so enmeshed in the debates over freedom of expression during the past decade and stood out so clearly in terms of the size of media coverage? Previous research has shown that the cartoons spurred debate because they lent themselves readily to the aims of strategic interest groups and could fit in with existing and emergent media logic (Eide, Kunelius, & Phillips, 2008;Hussain, 2007;Sniderman et al, 2014). In the cartoon controversies, different justifications rub against each other, spurring reactions, both violent and non-violent.…”
Section: Resultsmentioning
confidence: 99%
“…This is unsurprising, because the controversy was not only created in and by news media, but also constituted as a media event, in several senses. First, the controversy was diffused, accelerated and turned into an international and transnational event by news media, not only in terms of the spread of the images in the first place and representation of ensuing reactions in the Muslim world and elsewhere, but also in terms of the mobilizing function, indeed at times the independently acting and politicizing role of news media (Douai, 2007;Hussain, 2007;Olesen, 2006a). Olesen's article in this issue pays particular attention to the role of media in transnational diffusion as 'trans-space communication with an indirect relationship between authors and audiences' where 'media disconnects claims from their authors and make them available to large undefined audiences'.…”
Section: Disciplinary Receptions Of the Cartoons Controversy And Thementioning
confidence: 99%